Tailoring Fe(VI) coordination microenvironment for high-efficiency oxidation: ligand-driven electron transfer and polymerization steering - Zhi Gao; Yu-Lei Liu; Zhuang-Song Huang; Xiao-Na Zhao; Xian-Shi Wang; Zi-Yi Han; Chong-Wei Cui; Jun Ma; Lu Wang (npj Clean Water)
Abstract Utilizing ligand-mediated homogeneous catalysis to enhance oxidant-driven pollutant removal efficiency presents significant research value while posing substantial challenges. This study utilized ethylenediaminetetraacetic acid (EDTA) to alter the coordination environment of ferrate(VI), thereby steering electron transfer and the phenoxylation pathways to enhance the pollutant removal, which is realized by the complexation-mediated regulation for kinetics and thermodynamics. For example, the introduction of EDTA increased the rate constant of ferrate(VI) oxidizing phenol by four times (from 50.79 M−1 s−1 to 208 M−1 s−1) and the stoichiometric ratio (∆[phenol]/∆[K2FeO4]) from 0.17:1 to 0.22:1. Theoretical calculation and experimental characterization proved that the in-situ formed metastable Fe(VI)-EDTA complex facilitates the electron transfer from Fe(VI) to benzene ring and the phenoxylation pathways. Consequently, the related polymerization products were produced in greater quantities (about 5 times) and with broader diversity than Fe(VI) alone. In the application to real water, the introduction of EDTA reduced more than half of ferrate(VI)’s dosage previously required for completely removing phenol. This study presents a novel strategy for optimizing ferrate(VI) oxidizing pollutants in water treatment, which presents notable environmental benefits by minimizing ferrate(VI) consumption and enhancing pollutant removal efficiency.